The taxonomy and biology of a new species Pontonema (Nematoda, Oncholaimidae) dominant in organically polluted sublittoral sediments around Scotland, with a review of the genus - Bett, B. J.; Moore, C. G. (Journal of Natural History, 1988)
A new species of free living marine nematode, Pontonema alaeospicula sp. nov., is a dominant member of the fauna in three organically polluted sublittoral habitats off the Scottish coast. The species is described and the genus reviewed. A schematic pictorial key to the genus is provided. Some notes on the biology of P. alaeospicula sp. nov. are given, based on initial studies of the population in situ and in laboratory culture.
NeMys doc_id: 16814